Pengukuran Kualitas Layanan Perpustakaan: Studi Pada Perpustakaan STIE Ekuitas Bandung - Asep Saeful Rohman (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2020)
This study aims to determine the extent of the quality of library services STIE Ekuitas Bandung. Service quality is seen based on the comparison between the services received by users and their expectations of library services. The scope of the research is on aspects of the attitude of officers (librarians) in serving (Affect of Service), access to information (Information Control), and the library as a place. The method used is a survey with a quantitative approach. Data collection was carried out using questionnaires, interviews, observations, and literature studies. The population of this research is the library members totaling 1594 students. By using non-probability sampling techniques and Yamane sample calculation formula obtained a number of 99 respondents. Data analysis uses the LibQual™ Model by measuring the gaps of services received and services expected by users. Based on the results of the study note that the average service quality is at the tolerance limit. This means that the STIE Ekuitas Bandung Library service received by users is considered quite good by users, which is above the minimum expected number. Another finding is that the library is still not maximal in providing superior services, namely services that are in accordance with the maximum expectations desired by the user.